(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the technologies and methodological foundations for organizing competitions in Paralympic sports within the framework of the New Uzbekistan Development Strategy. The study is based on the idea that contemporary Paralympic competitions should be designed not only as sporting events, but also as an inclusive pedagogical, social, and organizational mechanism that promotes equal participation, human dignity, and the development of adaptive physical culture. The paper analyzes the structural components of competition organization, including regulatory planning, classification procedures, athlete preparation, venue accessibility, medical and psychological support, officiating, digital management tools, safety control, and volunteer coordination. Particular attention is given to the integration of educational institutions, sports organizations, local communities, and public administration bodies in creating an effective competition environment for athletes with disabilities. The article argues that in the conditions of national modernization, Paralympic sport serves as an important platform for strengthening social inclusion, civic engagement, and value-based education. The proposed approach interprets competition technologies as a system of interrelated pedagogical and managerial actions aimed at ensuring fairness, accessibility, transparency, and high organizational quality. The findings support the view that the effective organization of Paralympic competitions contributes to the implementation of strategic national priorities related to human capital development, inclusive education, public health, and the expansion of adaptive sports opportunities.